(3OQGSI ejOGfjIs - (3eMehO(B, (3YQGHis ((3GdbGgQI(B:s (3GdOGQ GdKbGajI ddfTQ(B,s, 2006)
(3jVe GdTHGH hKbGaI GdYhdeI, GdYhdeI hGdKbGaI GdEbJUGOjI ddTHGH, GdYhdeI hGdLhGfH GdELJeGYjI aj KbGaI GdTHGH, JCKjQGJ GdYhdeI Ydi GdKbGaI GdOjfjI ddTHGH, GdYhdeI hGdKbGaI GdSjGSjI ddTHGHs
Keywords: (3GdKbGaIs; (3GdTHGH(B- (3GdJfejI GdKbGajIs; (3GdYhdeIs